Perception of Gay Men as Defectors and Commitment to Group Defense Predict Aggressive Homophobia - Florian van Leeuwen; Helena Miton; Rengin B. Firat; Pascal Boyer (Evolutionary Psychology, 2016)
Homophobia encompasses a variety of attitudes and behaviors with distinct causal paths. We focus on aggressive homophobia, a propensity to feel anger and express aggression toward gay men. We investigated the conjecture that homosexual males might be seen, in recent Western cultures, as defectors from collective group defense. We predicted that consistent with a functional motive to punish and deter free riding, the perception of gay men as defectors would motivate aggression toward gay men. We also predicted that individuals with greater commitment to group defense might show more aggressive homophobia (as these individuals have more to lose from the defection than individuals who are not committed to group defense). Study 1 showed that aggressive homophobia correlated positively with the tendency to implicitly associate gay men with defection from group defense. Study 2 showed that a tendency to punish homosexual males for a theft correlated positively with commitment to group defense. The findings suggest that coalitional psychology might contribute to explaining the existence and quality of certain kinds of social stigma.